Valsalva-Induced Orbital and Subcutaneous Periorbital Emphysema Secondary to Lamina Papyracea Dehiscence: A Case Report - Stuti Misty Tanya; Merve Kulbay; Femida Kherani; Marc B. Mydlarski (Case Reports in Ophthalmology)
Introduction: Pneumo-orbit and periorbital subcutaneous emphysema secondary to defects in the sinus wall have been well described in the context of traumatic or surgical sequelae. However, these conditions may rarely occur atraumatically in the setting of an idiopathic or congenital sinus wall dehiscence, with a risk for orbital compartment syndrome and irreversible vision loss. We describe a case of idiopathic lamina papyracea dehiscence with resultant pneumo-orbit and elevated intraocular pressure. Case Presentation: A 28-year-old man experienced a sudden onset of unilateral orbital and subcutaneous periorbital emphysema following Valsalva maneuver. He had unilateral subcutaneous emphysema, crepitus, violaceous discoloration of the lids, and chemosis of the palpebral conjunctiva. Visual acuity was intact, and intraocular pressure was mildly elevated. Imaging showed an idiopathic lamina papyracea dehiscence. The patient was advised of sinus precautions with uneventful spontaneous resolution and no visual sequelae. Conclusion: Lamina papyracea dehiscence predisposes to spontaneous Valsalva-induced orbital or periorbital emphysema with a risk of elevated intraocular pressure, optic neuropathy, and vision loss; prompt recognition and early management can prevent vision-threatening sequelae.